A qualitative study of barriers and facilitators to the implementation of a pilot school-based, toothbrushing programme - Ming-Ching Wang; Zoe Marshman; Wei-Han Chen; Wen-Yu Shih (BMC, 2022)
Abstract Background While supervised toothbrushing programmes have been established in many countries of the world, little is known about different perspectives on their implementation. The aim of the study was to explore stakeholders' barriers and facilitators to implementation of a school-based toothbrushing programme in Taiwan. Methods Focus groups and interviews were used to explore the views of elementary school students, teachers, staff, and nurses in a piloted school-based toothbrushing programme. The topic guides were developed according to the Theoretical Domains Framework (TDF) to cover the behavioural factors systematically and comprehensively. Data were analysed with content analysis. Results Overall, 36 students, 29 teachers/staff, and five school nurses (N = 65) were included. The overarching theme was the importance of habit formation for both staff and children to ensure that toothbrushing as part of the programme was embedded into the school schedule and routine. While children did not necessarily appear to retain the dental knowledge which was taught in the programme, the provision of fluoride toothpaste and toothbrush for their use in schools allowing teachers and staff to choose the timing of the brushing and engaging classmates to supervise each other were found to be key factors. Conclusions Implementing a school-based toothbrushing programme with the support of staff and active engagement of children can help children to develop a toothbrushing habit. Classmate-supervised toothbrushing may reduce the burden on teachers and staff to implement the programme.